Comparative research of intestinal microbiota diversity and body mass regulation in Eothenomys miletus from different areas of Hengduan mountain regions - Yan, Bowen; Jia, Ting; Wang, Zhengkun; Zhu, Wanlong (Frontiers in Microbiology, 2022)
In order to investigate the effects of different areas on intestinal bacterial diversity and body mass regulation in Eothenomys miletus from Hengduan mountain regions, and to explore the community structure and diversity of intestinal microflora and their role in body mass regulation. E. miletus was collected from five areas including Deqin (DQ), Xianggelila (XGLL), Lijiang (LJ), Jianchuan (JC) and Dali (DL), we used 16SrRNA sequencing technology combined with physiological and morphological methods to study the intestinal microbiota diversity, abundance and community structure of the intestinal bacteria in winter, and to explore the influence of geographical factors, physiological indicators including food intake, resting metabolic rate (RMR), non-shivering thermogenesisg (NST), neuropeptide Y (NPY), Agouti-Related Protein (AgRP) proopiomelanocortin (POMC), cocaine and amphetamine regulated transcription peptide (CART), and morphological indicators including body mass, body length and other 9 indicators on the intestinal microflora diversity in E. miletus. The results showed that there were significant differences in metabolic indexes such as RMR, NST, NPY, AgRP, and morphological indexes such as body length, tail length and ear length among the five regions. Bacterial community in the intestinal tract in E. miletus mainly includes three phyla, of which Firmicutes is the dominant phyla, followed by Bacteroidetes and Tenericutes. At the genus level, the dominant bacterial genera were S24-7(UG), Clostridiales (UG) and Lachnospiraceae (UG), etc. The α diversity of intestinal microorganisms in DL and JC were significantly different from that in the other three regions. Genera of intestinal microorganisms in DL and JC were also the most. Moreover, Bacteroides, Ruminococcus and Treponemacould affect energy metabolism in E. miletus, which were closely related to the environment in which they lived. All of these results indicated that different areas in Hengduan Mountain had certain effects on the structure of intestinal microbial community in E. miletus, which were responded positively to changes in food abundance and other environmental factors. Furthermore, Firmicutes and Bacteroidetes play an important role in the body mass regulation in E. miletus.